2017
DOI: 10.1186/s13705-017-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Democratic institutions and the energy intensity of well-being: a cross-national study

Abstract: Background: Energy consumption is necessary for human well-being, yet the growth of energy consumption also contributes to climate change and a range of negative externalities. Thus, a key sustainability challenge is to efficiently use energy consumption to promote human well-being. This manuscript contributes to the growing literature on the ecological intensity of well-being (EIWB) by modeling the relationship between democratic institutions and the energy intensity of well-being. Methods: We use internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 89 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Findings suggest that the effect of GDP per capita on CIWB is relatively large, positive, and stable in magnitude through time for nations in North America, Europe, and Oceania, and has increased in magnitude through time for nations in the other regional samples of nations (Jorgenson 2014; see also Dietz 2015;Dietz et al , 2012Mayer 2017;Mazur and Rosa 1974).…”
Section: Economic Growth and Cyclesmentioning
confidence: 97%
“…Findings suggest that the effect of GDP per capita on CIWB is relatively large, positive, and stable in magnitude through time for nations in North America, Europe, and Oceania, and has increased in magnitude through time for nations in the other regional samples of nations (Jorgenson 2014; see also Dietz 2015;Dietz et al , 2012Mayer 2017;Mazur and Rosa 1974).…”
Section: Economic Growth and Cyclesmentioning
confidence: 97%
“…For instance, Adom (2016) suggested that it is challenging for countries to emerge from an energy-inefficient condition due to broken institutions, inadequate infrastructure, weak regulatory systems, and entrenched corruption. Further research on the impact of democratic institutions on well-energy being's intensity by Mayer (2017) revealed that democracy does not seem to increase energy intensity. Deacon (2009) discovered that non-democratic governments often provide access to public assets like energy infrastructure at costs that are far higher than those of democratic organizations.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, it is necessary to subtract a constant from the numerator to balance the variation coefficient of the numerator and the denominator. This method is widely used in the studies of EIWB [30,31]. The basic mathematical basis for this is that subtracting a constant from the numerator reduces the mean without changing the standard deviation of the numerator, thereby equalizing the variation coefficients in the numerator and denominator.…”
Section: The Measurement Of Eiwbmentioning
confidence: 99%